A bioactive product lipoxin A4 attenuates liver fibrosis in an experimental model by regulating immune response and modulating the expression of regeneration genes - Kurtoğlu, Elçin Latife; Kayhan, Başak; Gül, Mehmet; Kayhan, Burçak; Akdoğan Kayhan, Meral; Karaca, Zeynal Mete; Yeşilada, Elif; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Lipoxin A4 (LXA4), an anti-inflammatory lipid mediator, regulates leukocyte cellular activity and activates gene transcription. The therapeutic effect of LXA4 on liver fibrosis and its mechanism on the immune system are largely unknown. Because the regenerative capacity of hepatocytes in acute and chronic liver failure models of mouse increases by silencing MKK4, we aimed to investigate the effect of parenteral administration of LXA4 on the genes responsible for regeneration of liver, namely MKK4, MKK7, and ATF2, and visualize the therapeutic effects in an experimental model.Materials and Methods: Fibrosis was induced in mice by administration of thioacetamide (TAA). LXA4 was administered during the last two weeks of fibrosis induction. The fibrosis level was measured by Knodell scoring. The liver function was measured by analyzing serum ALT, AST, and AP levels. Expression levels of genes responsible for liver fibrosis (TGF-α) and cell regeneration (MKK4, MKK7, and ATF2) have been measured by RT-PCR analysis. Inflammatory and anti-inflammatory cytokine levels were measured in serum samples and liver homogenates by Enzyme Linked Immunosorbent Assay (ELISA). Ultrathin sections were examined using a transmission electron microscope and analyzed.Results: We observed significant healing in liver of the LXA4-treated group, histologically. This finding was in parallel with reduction of serum ALT, AST, but not AP levels. TGF-α and MKK4 expressions were significantly reduced in the LXA4-treated group. Administration of LXA4 caused significant elevation of IL-10 in systemic circulation; however, that elevation was not detected in liver homogenates. Nevertheless, significant reductions in TNF-α and IL-17 have been observed.Conclusion: The anti-inflammatory effect of LXA4 maintains the regenerative capacity of liver during fibrosis in an experimental liver fibrosis model. LXA4 may be therapeutically beneficial in liver fibrosis.Cite this article as: Kurtoğlu EL, Kayhan B, Gül M, et al. A bioactive product lipoxin A4 attenuates liver fibrosis in an experimental model by regulating immune response and modulating the expression of regeneration genes. Turk J Gastroenterol 2019; 30(8): 745-57.